Microbial assessment of landscape garden watering using treated sewage effluent - Mohd. Said, Mohd. Ismid (Penerbit Universiti Teknologi Malaysia, 2008)
Among the types of wastewater reuses, plant watering was theearliest application and receives most of the attention. It can beused in parks, school yards, golf courses, cemeteries, and homelawns (Gerard, 1997). Globally, the use of sewage effluent invarious applications such as agricultural irrigation, industrial uses,and groundwater recharge have been studied and implemented inmany countries such as the USA, Germany, Japan, India, Australia,Israel and South Africa.